Reconstruction of the environmental quality fuzzy index - Roveda, José Arnaldo F. [UNESP]; Do Amaral Burghi, Ana Carolina [UNESP]; Roveda, Sandra R. M. M. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2013)
In the world stage, the environmental condition has been a big public policies issue. A clear understanding of the parameters that determine the state of the environment is essential for estimation of the quality of life of the population, not least since ecosystems are highly complex. Consequently, definition of public policies demands the use of evaluation tools that can combine and quantify information in a clear way. The use of indicators and indices that are able to translate the complexity of environmental conditions in cities into simpler terms has been increasingly effective in decision-making, since they assist in general evaluation of the situation in question, identification of priority actions and anticipation of future trends. In an attempt to evaluate the environmental conditions of the Brazilian city, Sorocaba, an Environmental Quality Fuzzy Index (IFQAmb) was proposed. In this work this methodology is improved. After reviewing the IFQAmb methodology, a number of changes in the index are proposed. Additional variables are suggested, derived from a State Environment Department program whose objective is to grant municipalities the title of 'Município Verde e Azul' (Green and Blue City). In addition, a new rule base is being drafted to enable consideration of all possibilities, since in the existing version the use of specific criteria eliminates a significant number of rules. The changes seek to define with clarity and precision the conceptual aspects and structure of the IFQAmb, so that it can provide an even more effective evaluation of environmental performance, guiding future actions in order to improve the living conditions of the population of Sorocaba. © 2013 IEEE.